2022
DOI: 10.1007/s00775-022-01942-7
|View full text |Cite
|
Sign up to set email alerts
|

Promising application of polyoxometalates in the treatment of cancer, infectious diseases and Alzheimer’s disease

Abstract: As shown in studies conducted in recent decades, polyoxometalates (POMs), as inorganic metal oxides, have promising biological activities, including antitumor, anti-infectious and anti-Alzheimer's activities, due to their special structures and properties. However, some side effects impede their clinical applications to a certain extent. Compared with unmodified POMs, POM-based inorganic-organic hybrids and POM-based nanocomposite structures show significantly enhanced bioactivity and reduced side effects. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 103 publications
(161 reference statements)
0
11
0
Order By: Relevance
“…Furthermore, several previous studies reported that the oral administration of POMs is presumed safe with a low risk of negative health effects. , For instance, polyoxotungstates show a potential antitumor activity and lower toxicity in vitro as well as in vivo experiments . Especially, vanadotungstates and polyoxovanadates have evidenced a good antitumor activity against some human cancer cells (MCF-7 human breast cells, HepG2 hepatocellular carcinoma cell, etc.)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, several previous studies reported that the oral administration of POMs is presumed safe with a low risk of negative health effects. , For instance, polyoxotungstates show a potential antitumor activity and lower toxicity in vitro as well as in vivo experiments . Especially, vanadotungstates and polyoxovanadates have evidenced a good antitumor activity against some human cancer cells (MCF-7 human breast cells, HepG2 hepatocellular carcinoma cell, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…Especially, vanadotungstates and polyoxovanadates have evidenced a good antitumor activity against some human cancer cells (MCF-7 human breast cells, HepG2 hepatocellular carcinoma cell, etc.) with low general cytotoxicity. , In addition, they are considered inhibitors of SERCA and PMCA Ca2+-ATPase , as well as bioactive target agents for Alzheimer’s diabetes and infectious disease treatments. …”
Section: Resultsmentioning
confidence: 99%
“…Due to the different signaling involved in cell death pathways between tumor cells and normal cells, it is possible to design POM drugs that have better selectivity by adjusting the ratio of the vanadium and tungsten atoms. On the other hand, the introduction of organic parts into the POMs framework could change its surface, charge, polarity and REDOX properties, resulting in the further reduction of cytotoxicity to normal cells [20,21] . The results showed that all the POMs have higher TI value as compared to the two approved drugs 5‐FU and Gemcitabine.…”
Section: Resultsmentioning
confidence: 99%
“…The negative charge, three‐dimensional shape and high polarity of POMs enable specific interactions with positively charged protein surfaces [12] . These interactions have been linked to the well‐documented biological properties of POMs, such as antibacterial, antiviral, antiprotozoal, antidiabetic, and anticancer activity [6, 13, 14] . Additionally, the favorable binding of POMs to protein surfaces renders them ideally suited for facilitating the crystallization of proteins and solving their structures through X‐ray diffraction [15–17] .…”
Section: Introductionmentioning
confidence: 99%